Characterisation of a maize mutant deficient in antifungal kauralexin accumulation - Wighard, Sara (Department of Molecular and Cell Biology, 2018)
Fusarium verticillioides and Cercospora zeina are two economically important fungal pathogens of maize in Southern Africa. Phytoalexins are low molecular weight anti-microbial compounds produced in plants in response to pathogen infection. In maize, two classes of non-volatile terpenoid phytoalexins, viz. kauralexins and zealexins, play a role in fungal resistance. It has previously been shown that maize lines inoculated with either F. verticillioides or C. zeina induces kauralexin and zealexin accumulation. In addition, kauralexin metabolite accumulation and candidate kauralexin biosynthetic gene expression were highly correlated. In this study a mutant line with a Dissociation transposon element inserted into An2 was identified with the goal of stopping An2 from being expressed. The mutants were maintained in an inbred W22 maize line. Gene expression was compared between transposon-insertion mutants and wild type W22 at the seedling stage. A F. verticillioides and C. zeina inoculation assay was carried out on a segregating knock-down line. Phytoalexin accumulation, gene expression and disease susceptibility were subsequently examined in the mutants and wild type. F. verticillioides-inoculated mutants displayed significantly decreased kauralexin and zealexins accumulation and An2 gene expression. Fungal load and symptoms was greater in mutants than wild type controls. Kauralexin accumulation and An2 expression were negatively correlated with the quantified fungal load. C. zeina-inoculated mutants did not display significantly reduced kauralexin accumulation and An2 expression as An2 did not appear to be upregulated in the W22 maize line in response to C. zeina. This is likely due to a genetically-controlled leaf flecking phenotype in W22 leading to broad-spectrum resistance, as well as potentially impacting the jasmonic acid pathway. Lastly, an attempt was made to clone An2 towards A. thaliana transformation for overexpression analysis. Only a truncated section of An2 was able to be cloned into the expression vector.